Bidding Strategies for Energy Storage Participation in Electricity Market Considering Uncertainty of Wind Power and Carbon Trading - ZHANG Xianwen, YIN Gaowen, SHEN Feifan, HUANG Sheng, WEI Juan (Shanghai Jiaotong Daxue xuebao)
Power side energy storage is a powerful tool for promoting the consumption of new energy and implementing the “dual carbon” strategy. In view of the imperfection of the bidding mechanism of the power side energy storage as an emerging entity participating in the competitive joint electricity market, and starting from the game relationship of the power side energy storage as a price maker participating in the spot electricity market, a bidding game two-level optimization model of the power side energy storage participating in the multi scenario application of the electric energy and reserve ancillary service market is proposed, considering the uncertainty of wind power output and the coupling of the electricity market with the introduction of carbon trading. The energy storage at the upper power supply side, as a leader, makes bidding decisions with the goal of maximizing its own comprehensive income, while the lower power trading center as a follower completes market clearing with the minimum cost of social power purchase and balance regulation. The MATLAB simulation verifies the rationality and effectiveness of the proposed model in optimizing the participation of power side energy storage in multi scenario application bidding in the electricity market and improving the comprehensive operating income of the energy storage.